Exploring the Nutrition-Related Health of the Ageing Population in Fiji: A Narrative Review - Salanieta Naliva MPH; Marlena Kruger PhD; Palatasa Havea PhD; Carol Wham PhD (SAGE Publishing, 2024)
Fijis' older population aged 55 years and over makes up 14% of the total population and is expected to reach 20% by 2050. This narrative review aimed to examine the health and nutrition status of the aging population of Fiji and sociodemographic determinants. A search strategy was conducted throughout databases, and gray literature from relevant websites was searched. Due to the limited evidence regarding the nutrition, health, and socio-economic factors that impact the aging population in Fiji the inclusion criteria were broad and included both genders (male and female), all publications up until December 2022, all study designs, and gray literature (government/institutional reports, conference proceedings, guidelines, Act, and Policies) . There was no filter for date applied in the search criteria. Studies that did not meet the search criteria were excluded. 20 documents including published articles were included for analysis and result synthesis. Life expectancy at birth for the Fiji population is 68 years. A significant annual increase in mortality rate from endocrine, nutritional, and metabolic diseases has been observed in women aged 75+ but not older men. Women of low-income status are more at risk than men. However, as most investigations aggregate those ≥18 years, there is a lack of information on older adults (≥65 years) health and nutrition status. To improve the health status of older adults, an understanding of the nutritional status of older adults is warranted, especially concerning lifestyle and sociodemographic determinants.